Screening for hand dermatitis in healthcare workers: Comparing workplace screening with dermatologist photo screening. (18th March 2019) - Nichol, Kathryn; Copes, Ray; Kersey, Karon; Eriksson, Jonas; Holness, Dorothy L.
Abstract : Background: Healthcare workers are at increased risk for occupational contact dermatitis, owing to wet work exposure. Early detection and management improves outcomes. Although several diagnostic tools are available, none is appropriate for rapid screening. Objectives: To assess the validity and feasibility of the Hand Dermatitis Screening Tool in the acute healthcare sector. Methods: Screening of 508 employees at three hospitals in Ontario, Canada was performed with the Hand Dermatitis Screening Tool either by an occupational health nurse ( N  = 225) or by self‐administration ( N  = 283). Two occupational dermatologists rated photographs of participants' hands. Results: Of the participants, 30.5% screened positive for hand dermatitis. A positive screen was associated with wet work, history of eczema, dermatitis, or other rash, and currently having a rash. Ninety‐four per cent of participants reported that using the tool took <2 minutes, 99% indicated that the tool was easy to use, and 86% stated that workplace screening was very important. Workplace and dermatologist photo screening showed fair agreement. Conclusions: The prevalence of hand dermatitis and identified risk factors were consistent with the literature. These findings, along with positive feasibility results, support further testing of the tool despite only fair agreement between workplace and dermatologist screening.